Grammatical Metaphor on the Students’ Writing Research Paper; A Systemic Functional Linguistics - Tampubolon, Sahlan; Sidabutar, Usman (Universitas Pahlawan Tuanku Tambusai, 2025)
The difficulties of writing research paper devokes grammatical metaphors in the perspectives of SFL to be applied in academic writing. This paper presents the process type and functions of ideational grammatical metaphor towards the students' writing research paper. The research design was applied by descriptive qualitative deployed on the English students’ writing. The findings deployed the process type of nominalization in ideational grammatical metaphor on the students' research papers was dominant in the material process and relational process. The function realization of deployment in transcategorisation of process to thing is the highest frequency on the clauses and followed to transcategorisation of process to quality. The frequency shows that several weaknesses encompassing the ability to employ grammatical meanings and the use of lexical cohesion. The research present a strategy for English learners and teachers to enhance writing qualities and language detections as an innovation in managing lexical varieties.